2022
DOI: 10.1155/2022/5525780
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Decisions on Pricing and the Greenness Degree in Supply Chains under Single- and Cross-Distribution Channels of Green and Nongreen Products and Government Subsidies

Abstract: Rapid economic growth and industrialization have brought us material abundance and greater convenience, while also causing socio-environmental problems such as the rapid depletion of resources, unexpected natural disasters, and environmental destruction. For these reasons, environmental issues have attracted public and governmental attention around the world over the past few decades. As a result, environmental sustainability has become a critical indicator for evaluating the success and efficiency of supply c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A government subsidy is a type of financial assistance generally offered to promote designated economic and social policies [36]. Government subsidies can take the form of cash payments or the provision of intermediate goods and services at no cost or at nominal prices from governments to suppliers [37].…”
Section: Governmental Subsidy Programs In Supply Chainsmentioning
confidence: 99%
“…A government subsidy is a type of financial assistance generally offered to promote designated economic and social policies [36]. Government subsidies can take the form of cash payments or the provision of intermediate goods and services at no cost or at nominal prices from governments to suppliers [37].…”
Section: Governmental Subsidy Programs In Supply Chainsmentioning
confidence: 99%
“…In addition, they explored the role of government subsidies and found that subsidies reduce green products' price and promote the sales of green products. Similarly, Lee and Yoon [36] constructed a three-stage Stackelberg game framework to derive equilibrium decisions on pricing and greenness under different distribution channel structures. They also confirmed the positive effect of the government subsidy on the green supply chain.…”
Section: Green Supply Chain Managementmentioning
confidence: 99%